Tualang honey supplementation improves inflammatory and bone markers among postmenopausal breast cancer patients : a randomised controlled trial - Zaida Zakaria,; Wan Zuraida Wan Ab Hamid,; Mahaneem Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Honey is traditionally used among breast cancer patients in Malaysia with the belief that it can improve the overall health. Therefore, this study aims to determine the effects of Tualang honey supplementation on levels of inflammatory markers, bone markers and oestradiol among postmenopausal breast cancer patients. Seventy-two patients on anastrozole were recruited and randomly divided into two groups (n = 36/group, with or without 20 g/day of Tualang honey for 12 weeks). Levels of interleukin-1 beta (IL-1β), tumour necrosis factor alpha (TNF-α) and carboxy-terminal crosslinked telopeptide of type 1 collagen (CTX) at post-intervention with anastrozole, increased significantly compared to their corresponding levels at pre-intervention. Meanwhile, at post-intervention with anastrozole+honey, procollagen type 1 amino-terminal propeptide level increased significantly, CTX level decreased significantly, with no change in inflammatory markers compared to their pre-intervention levels. In conclusion, Tualang honey supplementation prevented the increased inflammation, reduced bone resorption and increased bone formation without changes in oestradiol level.